2012
DOI: 10.1007/s10637-012-9808-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of bevacizumab and erlotinib in the treatment of advanced hepatocellular carcinoma patients with sorafenib-refractory disease

Abstract: SummaryBackground The combination of bevacizumab (B) and erlotinib (E) has shown promising clinical outcomes as the first-line treatment of advanced HCC patients. We aimed to evaluate the efficacy and safety of using combination of B + E in treating advanced HCC patients who had failed prior sorafenib treatment. Methods Eligible advanced HCC patients with documented radiological evidence of disease progression with sorafenib treatment were recruited. All patients received bevacizumab(B) at 10 mg/kg every 2 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 30 publications
2
50
0
1
Order By: Relevance
“…study with 50 ad- Combinational therapy 5-fluorouracil plus sorafenib [46] Phase Ⅱ 39 SD: 46.2%; median TTP: 8 mo; OS: 13.7 mo Tegafur/uracil plus sorafenib [47] Phase Ⅱ 53 Median PFS: 3.7 mo; median OS: 7.4 mo Octreotide plus sorafenib [48] Phase Ⅱ (So.LAR.) 50 SD: 66%; median TTP: 7.0 mo; median OS: 12 mo Doxorubicin plus sorafenib vs doxorubicin plus placebo [50] Phase Ⅲ 47 vs 49 Median TTP: 6.4 mo vs 2.8 mo; OS: 13.7 mo vs 6.5 mo; PFS: 6.0 mo vs 2.7 mo Erlotinib plus sorafenib vs erlotinib plus placebo [53,54] Phase Ⅲ (SEARCH) 362 Median TTP: 3.2 mo vs 4.0 mo; OS: 9.5 mo vs 8.5 mo Second-line treatments Sunitinib [55] Retrospective analysis 11 SD: 40%; median TTP: 3.2 mo Brivanib [56] Phase Ⅱ 46 SD: 41.3%; RR: 4.3%; DCR: 45.7%; median OS: 9.79 mo Tivantinib vs placebo [6] Phase Ⅱ 71 vs 36 Progressive disease: 65% vs 72%; TTP: 1.6 mo vs 1.4 mo Gemcitabine plus oxaliplatin [59] Retrospective analysis 18 Overall RR: 18.8%; SD: 18.8%; median PFS: 3.2 mo; OS: 4.7 mo Erlotinib plus bevacizumab [61] Phase controlled arm in this trial, the encouraging outcome was unable to justify that the efficacy was from sorafenib alone or the synergism with doxorubicin. Now, a randomized phase Ⅲ trial aiming to evaluate the combinational therapy of doxorubicin plus sorafenib compared with sorafenib alone is recruiting participants (ClinicalTrials.…”
Section: Combinational Therapy With Sorafenibmentioning
confidence: 99%
See 2 more Smart Citations
“…study with 50 ad- Combinational therapy 5-fluorouracil plus sorafenib [46] Phase Ⅱ 39 SD: 46.2%; median TTP: 8 mo; OS: 13.7 mo Tegafur/uracil plus sorafenib [47] Phase Ⅱ 53 Median PFS: 3.7 mo; median OS: 7.4 mo Octreotide plus sorafenib [48] Phase Ⅱ (So.LAR.) 50 SD: 66%; median TTP: 7.0 mo; median OS: 12 mo Doxorubicin plus sorafenib vs doxorubicin plus placebo [50] Phase Ⅲ 47 vs 49 Median TTP: 6.4 mo vs 2.8 mo; OS: 13.7 mo vs 6.5 mo; PFS: 6.0 mo vs 2.7 mo Erlotinib plus sorafenib vs erlotinib plus placebo [53,54] Phase Ⅲ (SEARCH) 362 Median TTP: 3.2 mo vs 4.0 mo; OS: 9.5 mo vs 8.5 mo Second-line treatments Sunitinib [55] Retrospective analysis 11 SD: 40%; median TTP: 3.2 mo Brivanib [56] Phase Ⅱ 46 SD: 41.3%; RR: 4.3%; DCR: 45.7%; median OS: 9.79 mo Tivantinib vs placebo [6] Phase Ⅱ 71 vs 36 Progressive disease: 65% vs 72%; TTP: 1.6 mo vs 1.4 mo Gemcitabine plus oxaliplatin [59] Retrospective analysis 18 Overall RR: 18.8%; SD: 18.8%; median PFS: 3.2 mo; OS: 4.7 mo Erlotinib plus bevacizumab [61] Phase controlled arm in this trial, the encouraging outcome was unable to justify that the efficacy was from sorafenib alone or the synergism with doxorubicin. Now, a randomized phase Ⅲ trial aiming to evaluate the combinational therapy of doxorubicin plus sorafenib compared with sorafenib alone is recruiting participants (ClinicalTrials.…”
Section: Combinational Therapy With Sorafenibmentioning
confidence: 99%
“…To evaluate the effects of erlotinib in combination with bevacizumab as secondline therapy after the failure of sorafenib, a phase Ⅱ trial is ongoing (ClinicalTrials.gov, NCT01180959). However, another similar phase Ⅱ trial executed during the same period showed disappointing interim results [61] . Among the ten recruited patients after first-line sorafenib treatment, no response or SD were achieved and the median TTP and OS was 1.81 and 4.37 mo, respectively.…”
Section: Second-line Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although VEGFRs were postulated as mediators of sorafenib response in HCC, testing for VEGF-A serum levels was not found to be predictive of sorafenib treatment success ( 10 ). Moreover, bevacizumab, an antibody against VEGF-A, only shows minimal responses in HCC (17)(18)(19)(20). A possible explanation for this is that the mechanism of action of sorafenib is predominantly independent of VEGF-A inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR antagonists were effective in human HCC cells (18). Gefitinib and erlotinib, two clinically approved EGFR chemical inhibitors, are used for the treatment of advanced HCC (20)(21)(22)(23)(24)(25). However, some studies have demonstrated the resistance to EGFR inhibitors in human HCC cells (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%